STRATEGI ORANG TUA DALAM MEMBINA PERILAKU ISLAMI REMAJA DI DESA AIR KEMUNING KEC. SUKARAJA KABUPATEN SELUMA - Yuliani, Herti; Zulkarnain; Nasution, Adam (Yayasan Darussalam Bengkulu, 2020)
This research is motivated by seeing that adolescence is still very fast causing various negative things such as this condition, if it is not immediately addressed it can continue into adulthood and can develop in a more negative direction, therefore the role of parents in fostering adolescent Islamic behavior is very necessary. . This type of research is descriptive qualitative research. By considering the setting in Air Kemuning Village, Sukaraja District, Seluma Regency. Subjects and informants in this study amounted to 30 consisting of 15 parents and 15 adolescents. In this research data collection technique using observation, interviews, and documentation. Based on the results of the research that has been done, it can be concluded that the strategies for fostering Islamic behavior are understanding, practice, habituation, rational, and emotional. 1) Understanding, given so that teenagers understand the existence of God as the source of life. Parents try from an early age to provide understanding and knowledge about Islamic behavior. 2) Practice, is done by giving examples to teenagers. That way teenagers will judge and follow. Practice is done and starts from simple things. 3) Habituation, carried out in everyday life by providing opportunities for children/students to behave well in accordance with Islamic teachings. 4) Rational, Parents teach about good behavior and bad behavior in life. Teach about good things and bad things, and tell the impact of every action. 5) Emotional, feelings or emotions of adolescents in carrying out behavior in accordance with religious teachings. Telling life experiences to children and providing useful advice